Answer:
Step-by-step explanation:
Mass of the person in elevator
M = 95.1kg
a. When the elevator is accelerating upward at 2.48m/s²
Fnet = ma
R — W = ma
R — mg = ma
R = ma+mg
R = m(a+g)
R = 95.1(2.48+9.81)
R = 95.1 × 12.2
R = 1168.78N
b. Elevator moving upward at a constant speed
This means that it is not accelerating. Therefore, the acceleration is zero
Fnet = ma
a = 0
Fnet = 0
R - W = 0
R = W
R = mg
R = 95.1 × 9.81
R = 932.931 N.
c. Elevator accelerating downward at 1.84m/s².
Fnet = ma
Since it is downward, a is moving in -ve direction of y axis
R — W = -ma
R = W—ma
R = mg —ma
R = m(g-a)
R = 95.1(9.81—1.84)
R = 95.1 × 7.97
R = 757.947 N.